Respostas
respondido por:
3
an=a1+(n-1)r
a1=2
r=5
an=2+(n-1)5
an=2+5n-5
an=-3+5n
a1=2
r=5
an=2+(n-1)5
an=2+5n-5
an=-3+5n
respondido por:
3
a1 = 2
a2 = 7
r = a2 - a1
r = 7 - 2
r = 5
an = a1 + (n - 1).r
an = 2 + (n - 1).5
an = 2 + 5n - 5
an = 2 - 5 + 5n
an = - 3 + 5n
an = 5n - 3
a2 = 7
r = a2 - a1
r = 7 - 2
r = 5
an = a1 + (n - 1).r
an = 2 + (n - 1).5
an = 2 + 5n - 5
an = 2 - 5 + 5n
an = - 3 + 5n
an = 5n - 3
claudianemary2:
obrigado
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás